The nexus of economic growth and environmental performance in Malaysia - Tze, San Ong; Adedeji, Babatunji Samuel; Kah, Kah Cheah; Chee, Leong Tan; Boon, Heng Teh; Masoud, Joseph (Universiti Malaysia Terengganu, 2021)
This study aims to investigate the relationship between economic growth and the Environmental Performance Index. It also seeks to assess the trend of economic growth and environmental performance. This research uses a quantitative research method. The data for economic growth and environmental performance index in Malaysia are extracted from the World Bank and Yale Environmental Performance Index, respectively, from 2002 to 2017. The findings indicate that Gross Domestic Product growth has a significant and negative effect on the Environmental Performance Index. Population growth also showed a negative impact on environmental performance. However, there is a positive relationship between Foreign Direct Investment, agriculture added value, export goods and services, and environmental performance. The results of the study revealed that the low environmental performance index in Malaysia is caused by the growth in the manufacturing sector. This paper has added value from the perspective of enhancement of policymaking concerning public finance and environmental performance.